السياق ودوره في تأويل النص السردي رواية الحركي لمحمد بن جبار أنموذجا - بن خناثة,فيروز (University of Eloued جامعة الوادي, 2024)
Abstract: Through this paper , we aim to emphaize the role that context plays, as the most important theories of semantics and text linguistcs, in directing meaning within the fictional text ; through an interpretive approach to the novel “AL-HARKI ” by MOHAMAD BEN JABBAR ,which is fertile ground for exploiting context data at its various levels , as it the focus was on the internal and external circumstances that led to the formation of the narrative content , and perhaps the interpretive approach is one of the most needed approaches for the context to demarcate is boundaries , pursue paths of meaning and cross into the inner world of the novel , and revealing the implicit meanings spread within the novel . نروم من خلال هذه الورقة إلى التأكيد على الدور الذي يلعبه السياق كأهم نظريات علم الدلالة ، و لسانيات النص، في توجيه المعنى داخل النص الروائي ، من خلال مقاربة تاويلية لرواية " الحركي " لمحمد بن جبار التي تعد أرضية خصبة لاستثمار معطيات السياق بمختلف مستوياته ، حيث تم التركيز فيها على الظروف الداخلية والخارجية التي أدت إلى تشكل المضمون السردي ، و لعل المنهج التأويلي من أكثر المناهج حاجة للسياق لترسيم حدوده ، و ملاحقة مسارات المعنى والعبور إلى العالم الداخلي للرواية، و كشف المعاني المضمرة المبثوثة داخل الرواية
Keywords: السياق; المقام; التأويل; الدلالة; context; interpretation; meaning; position; significance